Application of Experiential Marketing as Brand Insight Development - Mandasari, Virginia; Hariyana, Nanik; Naufal, Ilham (Future Science, 2023)
Branding has become a very popular approach to managing and driving the development of products or services. To make the process more efficient, it is necessary to define the brand base correctly. One of the key elements in defining brand insight is consumer insight, which has recently become increasingly popular. The main prerequisite for the importance of consumer insight is dynamic changes in consumer needs and behavior, which determine their decisions. Customers not only judge products and services based on their quality but also through marketing strategies. Marketing strategies can be carried out aggressively through an experiential approach and an emotional approach to customers. Simultaneously, the author shows the strategic meaning of consumer insight in the process of forming brand insight to find the right branding according to the desired target market.